2016
DOI: 10.1007/s11284-016-1427-y
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of wood decomposer fungal activities and bryophytes on spruce seedling regeneration on coarse woody debris

Abstract: Decaying logs are important seedbeds in boreal and subalpine forests. However, biotic and abiotic factors and their interactions related to seedling colonization patterns on logs remain unclear. In the present study, we evaluated the influence of bryophyte communities, wood decay type (white‐, brown‐, and soft‐rot) owing to decomposer fungal activities, and environmental abiotic factors on seedling establishment in an old‐growth subalpine coniferous forest in Japan. Among the tree species recorded on the conif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Substrate pH is an important factor in the development of bryophyte communities (Gabriel & Bates, 2005), as it affects aspects of the performance of bryophyte species, such as spore germination (Wiklund & Rydin, 2004). Ando et al (2017) also reported that a liverwort, Scapania bolanderi, frequently dominated on brown-rotted P. jezoensis var. hondoensis logs, while a moss, Pleurozium schreberi, occurred on white-rotted spruce logs in subalpine coniferous forest.…”
Section: Bryophytesmentioning
confidence: 99%
“…Substrate pH is an important factor in the development of bryophyte communities (Gabriel & Bates, 2005), as it affects aspects of the performance of bryophyte species, such as spore germination (Wiklund & Rydin, 2004). Ando et al (2017) also reported that a liverwort, Scapania bolanderi, frequently dominated on brown-rotted P. jezoensis var. hondoensis logs, while a moss, Pleurozium schreberi, occurred on white-rotted spruce logs in subalpine coniferous forest.…”
Section: Bryophytesmentioning
confidence: 99%
“…Rodents and slugs have been found to disperse lichen and bryophyte propagules (Asplund et al., 2010; Barbé et al., 2016; Kimmerer, 1994; Kimmerer & Young, 1995), and mammals use fallen logs as trails through the forest, so it could be a combination of differences in propagule dispersal ability, germination requirements, and biotic interactions that determine these changes. Alternatively, different decomposer fungi could influence bryophyte community structure on nurse logs as found in alpine forests in Japan (Ando et al., 2017; Fukasawa et al., 2019). Thus, the influence of bryophytes on tree seedlings could be mediated by other biotic interactions through a trophic cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Rodents and slugs have been found to disperse lichen and bryophyte propagules (Asplund, Larsson, Vatne, & Gauslaa, 2010;Barbé et al, 2016;Kimmerer, 1994;Kimmerer & Young, 1995), and mammals use fallen logs as trails through the forest, so it could be a combination of differences in propagule dispersal ability, germination requirements, and biotic interactions that determine these changes. Alternatively, different decomposer fungi could influence bryophyte community structure on nurse logs as found in alpine forests in Japan (Ando, Fukasawa, & Oishi, 2017). Thus, the influence of bryophytes on tree seedlings could be mediated by other biotic interactions through a trophic cascade.…”
Section: Discussionmentioning
confidence: 99%